Contracted description of driven degenerate multilevel quantum systems - Xu, Xiangyu (2024)
We formulate a contraction theorem that maps quantum dynamics of a multilevel degenerate system (DS) driven by a time-dependent external field to the dynamics of the corresponding contracted non-degenerate system (CNS) of lower dimension, provided transitions between each pair of degenerate levels in the DS have identical transition dipole moments. The theorem is valid for an external field of any strength and shape, with and without rotating wave approximation in the system-field interaction. It establishes explicit relations between DS and CNS observables, significantly simplifies numerical calculations, and clarifies physical origins of the field-induced DS dynamics.